Strength and Stiffness of Wooden Building using Static Equivalent Analysis - Yosafat Aji Pranata (Wood Research Journal, 2025)
Wooden buildings can be used to support tourism infrastructure in the West Java region. This research aims to study the behavior of a wooden buildings due to designed earthquake loads. The function of the building is as a guest house. The scope used in the research are as follows the building functions as one of the tourism support infrastructure in Stamplat Village, Indragiri Village, Bandung Regency, West Java as a lodging building. The building uses a frame system concept with the main components being beams and columns of yellow Meranti wood (Shorea faguatiana). The size of the building is 30 m2. All cross-sections of beams and columns are rectangle. The static based shear load is calculated using equivalent static analysis. The stiffness (drift) is calculated according to Indonesian earthquake code SNI 1726:2019. Design the capacity of columns and beams (strength) using the reference to Indonesian wood code SNI 7973:2013. The research results show that the drift of the building due to the equivalent static earthquake load in the main direction of the building does not exceed the permit limits, the nominal capacity of the columns and beams meets the requirements and the value are lower than the maximum factored load combination. This research provides benefits, namely designing wooden buildings, even though the quality of the wood is limited, if designed properly, it can be used as an earthquake-resistant building.